Persilangan Kapitalisme dan Negara: Kerentanan Buruh Migran Perempuan dan Peran LSM LRC-KJHAM dalam Merespon Kerentanan di Kabupaten Grobogan Tahun 2023 - Tiara Azalia Zahra; Dewi Erowati (Journal of Politic and Government Studies, 2026)
This study examines the intersection of power relations between capitalism and the state in shaping the vulnerability of female migrant workers from Grobogan Regency, and analyzes the role of LRC-KJHAM as a civil society organization in responding to this vulnerability in 2023. In this study, capitalism is understood concretely through employment relations that place female migrant workers in a subordinate position, particularly in wage relations with suppliers and employers in destination countries, as well as through mechanisms that perpetuate the gender-based division of labor. Meanwhile, the state refers to the Grobogan Regency Regional Government and related agencies authorized to protect migrant workers. This study uses a qualitative approach through in-depth interviews, observation, and documentation with LRC KJHAM activists, active migrant workers, and former migrant workers in two assisted communities, namely Women Migrant Curut and Migrant Group Wedoro. The analysis is conducted using a Marxist feminist perspective and Mansour Fakih's NGO role theory. The research findings indicate that the vulnerability of female migrant workers is formed through two main mechanisms. First, the disciplining of women's bodies through limited access to local economic resources, domestication that narrows employment options in the care sector, and the internalization of false consciousness that limits women's participation in public spaces. Second, the exploitation of reproductive labor in migrant labor relations, reflected in wage cuts by providers, breaches of employment contracts, excessive workloads, and discriminatory and violent practices by employers in destination countries. In the context of the state's role, the findings indicate that the Grobogan Regency Government has not fully implemented its protection function optimally, particularly in providing access to decent work in the area of origin and in strengthening protection mechanisms before and after migration. This condition contributes to the continued structural vulnerability experienced by female migrant workers. In response to these conditions, LRC-KJHAM implemented three main strategies: organic intellectual creation through community discussions and participatory research, strengthening agency through paralegal training and economic access, and policy advocacy as a form of non-state social control. The conclusion of this study is that the vulnerability of female migrant workers is the result of structurally reproduced violence and the role of LRC-KJHAM demonstrates an ambivalent reformist tendency between challenging government hegemony and operating under the logic of development to attract donors.